Multidisciplinary simulation training for Australian perioperative teams: A qualitative descriptive exploratory study - Michelle Hibberson; Jessica Lawton; Dean Whitehead (Journal of Perioperative Nursing)
Background: Perioperative units are complex and high-risk environments where teams of multidisciplinary health care professionals work collaboratively. Multidisciplinary simulation training is a form of education that allows perioperative teams to practise the non-technical and technical skills essential for managing emergency events within the perioperative environment. Despite the benefits of multidisciplinary simulation training, there is a paucity of literature about it; therefore, this study examined the experiences of Australian multidisciplinary perioperative team members who had undertaken simulation training.